Echocardiographic Morphological Classification of Aortic Stenosis in Sulaimani Pediatric Teaching Hospital/Kurdistan/Iraq - Salih, Aso Faeq (Kurdistan Journal of Applied Research, 2017)
Aortic stenosis occurs when the heart’s aortic valve narrows. This narrowing prevents the valve from opening fully, which obstructs blood flow from the heart into the aorta and onward to the rest of the body. The aim of the study was to performed the echocardiographic study of the major morphological types of aortic valve stenosis in the pediatric cardiac unit in suliamani. A retrospective study including 127 patients aged from birth to 14 years done in the cardiac unit / Sulaimani pediatric teaching hospital. The data were collected from the recorded files of the patients examined in that unit during the period from 2006 to 2016.Collected data included name, age, sex, residency, consanguinity, clinical presentation, associated syndromes and Echo findings. Statistical analysis was performed by SPSS 21. Chi-square test was used to find out the correlation between categorical variables, P value of (? 0.05) was regarded significant. Overall, 80 were males (63%) and 47 were females (37%). Forty patients (31.5%) were below one year. The valvular type found in 96 cases (75.6%). subvalvular and supravalvular types found in 22 cases (17.3%), 9 cases (7.1%) respectively. We found 91 cases (94.8%) of bicuspid, 3 cases (3.1) of tricuspid and 2 cases (2.1%) of the unicuspid valve. In subvalvular type we found 14 cases (63.6%) of sub aortic ridge, 5 cases (22.7%) of tunnel type and 3 cases (13.6%) of systolic anterior motion. In supravalvular type we had 7 cases (77.8%) of hourglass and 2 cases (22.2%) of the long segment. Aortic regurgitation was the most common associated cardiac defect. There was a significant association between the types of aortic stenosis and the mild grade of AR; P value <0.05. In conclusion the valvular aortic stenosis was the most common type of aortic stenosis in this study. Bicuspid aortic valve found to be the most common congenital anomaly associated with aortic stenosis. Most of the patients with aortic stenosis were discovered to have an accidental murmur.